A cross sectional study to assess the anxiety, stress and depression among nurses during COVID-19 at selected hospitals, Udaipur - Pujari, Jitendra; Mansuri , M. U. (International Journal Of Community Medicine And Public Health, 2024)
Background: This study aims to assess anxiety, stress, and depression levels among nurses working during the COVID-19 pandemic. Methods: A quantitative non-experimental approach was employed, utilizing a descriptive cross-sectional design with 300 nurses selected through simple random sampling. Data collection included demographic and clinical variables. Anxiety, stress, and depression levels were measured using the Beck anxiety inventory (BAI), perceived stress scale, and Hamilton depression rating scale, respectively. Pearson's correlation and Chi-square tests were used for analysis in statistical package for the social sciences (SPSS). Results: A majority of staff nurses experienced mild anxiety (53.7%), stress (64.3%), and depression (71.7%). Scores indicated mean anxiety (14.42, SD=4.46), stress (13.74, SD=3.13), and depression (18.23, SD=4.23). Positive correlations were found between stress-anxiety (p=0.002, r=0.376) and anxiety-depression (p=0.040, r=0.119). A weak correlation existed between stress and depression (p=0.068, r=0.105). Anxiety correlated with age, professional experience, and marital status (p<0.05), while stress correlated with age and professional experience (p<0.05). Depression correlated with professional experience and marital status (p<0.05). Work-related variables and fears were associated with anxiety and stress but not depression among staff nurses during COVID-19. Conclusions: The study underscores widespread mild anxiety, stress, and depression among nurses during the pandemic, emphasizing their interconnection. Age, professional experience, and marital status influenced mental health outcomes. Tailored interventions and targeted support are crucial to address these challenges and enhance nursing well-being. Healthcare institutions should prioritize implementing such strategies to bolster nurses' resilience and effectiveness in navigating ongoing and future challenges.